Analysis of Elementary School Teachers' Readiness to Implement the National Assessment in Indonesia - Vitasari, Gerhani Nur; Hidayat , Muhamad Taufik (Universitas Ahmad Dahlan, 2025)
This study aims to assess the readiness of elementary school teachers in Boyolali Regency to implement the National Assessment (Asesmen Nasional or AN). Using a quantitative survey method with online questionnaires, data were collected from a sample determined by the Slovin formula and analyzed descriptively. Results show that 89% of teachers understand the AN well, 8% demonstrate deep comprehension, and 3% have limited understanding. Regarding readiness, 87% feel ready, 7% are ready, and 6% are not yet prepared. Overall, teachers in Boyolali show a satisfactory level of understanding and preparedness. However, a small group still needs further support. This study highlights the need for ongoing professional development to strengthen teacher competencies, particularly in response to changes in assessment policies. The findings provide valuable insights for policymakers and training providers in designing targeted interventions and offer a basis for further qualitative research on factors affecting teacher readiness.